Genogram: a tool for characterizing the families of adolescents parents in João Pessoa, Paraíba State, Brazil - 10.4025/actascihealthsci.v34ispec.11263 - Alice Iana Tavares Leite; Neusa Collet; Sonia Maria Könzgen Meincke; Telma Elisa Carraro; Débora Raquel Soares Guedes Trigueiro (Universidade Estadual de Maringá, 2012)
The study aimed to characterize the family composition of adolescent fathers in the city of João Pessoa, Paraíba State. This is a part of a multicenter survey developed in the states of Paraíba, Rio Grande do Sul and Santa Catarina. The population was composed of ten teenage fathers living in the urban area of João Pessoa. Data collection occurred from December 2008 to October 2010 through semi-structured interview and construction of the genogram and eco-map. Participants' age ranged from 16 to 19 years. They all lived with his partner and most had low education. The unemployed and those with income below one minimum wage indicated the family as the keeper of the home. Most fathers also depended on other family housing, and the amount of people living in the same house ranged from three to seven. Despite the existence of conflicting and/or distant relationships, all respondents reported that seek emotional and financial support in their own family. Fatherhood and motherhood in adolescence had already been experienced by some families. Understanding adolescent parents requires a broader view about composition and family dynamics, a task to be faced by health professionals committed to the care, being the genogram a viable and important tool in this process.